Egg to chicken - Tonkin, Rachel (Children's author); Coleman, Stephanie Fizer (New York : Crabtree Publishing Company, 2019)
"How does a chicken grow? Follow the journey through a chicken's life cycle, from the time the egg is laid, through hatching as a chick to becoming a fully grown hen"--
Includes index.
Ages 5-7.
K to Grade 3.
Keywords: Chickens -- Juvenile literature; Chickens -- Life cycles -- Juvenile literature; Chickens -- Development -- Juvenile literature